Housing in London: Operations by the County Council - W. J. A. (Quarterly Journal of Economics, 1900)
Journal Article Housing in London: Operations by the County Council Get access W. J. A. W. J. A. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 14, Issue 3, May 1900, Pages 432–434, https://doi.org/10.1093/qje/14.3.432 Published: 01 May 1900